2018
DOI: 10.1007/s10072-018-3439-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of sarcopenia and dynapenia according to stage in patients with idiopathic Parkinson’s disease

Abstract: In the early stages of chronic progressive diseases like IPD, identification of sarcopenia and dynapenia is important considering the limitations of disease-preventive effects in treatments applied after diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 35 publications
2
39
0
1
Order By: Relevance
“…Prevalence for sarcopenia in our cohort of PS patients was 13.5% (Table 1), i.e., >2-fold higher than in the normal German population. Studies investigating sarcopenia in iPD patients have found different prevalence rates, ranging from 6.6 to 25.9% (for a better comparison, mean values were calculated only for those studies that reported prevalence rates separated for gender) [10-13]. These variations in prevalence are based on different cut-off values for muscle mass, gait speed, and hand-grip strength as well as different methods for measuring muscle mass (BIA vs. dual-energy X-ray absorptiometry [DXA]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence for sarcopenia in our cohort of PS patients was 13.5% (Table 1), i.e., >2-fold higher than in the normal German population. Studies investigating sarcopenia in iPD patients have found different prevalence rates, ranging from 6.6 to 25.9% (for a better comparison, mean values were calculated only for those studies that reported prevalence rates separated for gender) [10-13]. These variations in prevalence are based on different cut-off values for muscle mass, gait speed, and hand-grip strength as well as different methods for measuring muscle mass (BIA vs. dual-energy X-ray absorptiometry [DXA]).…”
Section: Discussionmentioning
confidence: 99%
“…These authors used DXA for muscle mass measurement and it was an Asian cohort, so a comparison of absolute values should be avoided. In another study investigating the prevalence of sarcopenia in iPD patients, a lower SMI was found in the iPD group, although the difference did not reach significance [13]. The following 2 reasons may contribute to a higher muscle mass in iPD patients: continuous levodopa medication possibly leads to an increased release of growth hormones that have a strong anabolic effect on muscle [19, 20], and symptoms such as bradykinesia, rigidity, and tremor can “train” muscles comparably to sports activities [10].…”
Section: Discussionmentioning
confidence: 99%
“…PD patients are likely to experience nausea, dyspepsia, constipation, medication side effects, dysphagia, anorexia and depressive symptoms that cause reduced energy intake [14]. Thirdly, it has also been found that PD patients have lower levels of physical activity (in terms of amount and intensity) compared to healthy older adults [1517].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of falls is greater in this population compared to healthy individuals and those with other neurological diseases with high risk of falls such polyneuropathy, spinal disorders and multiple sclerosis [5]. It is very important to early detect sarcopenia and fall risk in PD patients because they can benefit from simple interventions such as high-protein diet and resistance exercise training [6].…”
Section: Introductionmentioning
confidence: 99%
“…We have read the article by Yazar et al [1] with interest. In this article, authors aimed to identify the incidence of sarcopenia and dynapenia according to disease stage among idiopathic Parkinson's disease patients.…”
Section: Dear Editormentioning
confidence: 99%